Impact of FDI on tax revenue in Pakistan - Haider Mahmood; A. R. Chaudhary (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
The study attempts to find the impact of foreign direct investment on tax revenue in Pakistan. Foreign direct investment and gross domestic product per person employed are used as independent variables and tax revenue is taken as dependent variable. Augmented Dickey Fuller, Phillips-Perron, Ng-Perron and Zivot-Andrews unit root tests are applied to find the level of integration in the time series. Auto-Regressive Distributive Lag and its error correction model are applied to find long run and short run relationships. The study finds the long run and short run relationships in the model. Foreign direct investment and gross domestic product per person employed have positive and significant impact on tax revenue. So, the study concludes the positive contribution of foreign direct investment in tax revenue in Pakistan.
Keywords: 330; FDI; tax revenue; cointegration; stationarity; Pakistan